Two new species of soft-winged flower beetles of the genus Kuatunia Evers, 1945–48 (Coleoptera, Malachiidae) from China and northeastern Russia - Tshernyshev, Sergei E. (Zootaxa, 2012)
Two new malachiid beetle species of the genus Kuatunia Evers are described: K. nordica sp. n., from Taimyr peninsula,northeastern Russia, and K. wolongensis sp. n., from China, Wolong Nature Reserve. Figures of male habiti, elytral ap-pendices, genitalia, and a distribution map for newly recorded species are given, and a determination key to all species of the genus is provided.